Comparison Conventional Coated Beam with Functionally Graded Coated Beam - Toudehdehghan, Abdolreza; Rahman, Md. Mujibur (International Journal of Engineering and Technology, 2018)
New materials are essential for the development and advancement in material manufacturing technology. A brief overview of the history of human civilization shows that from stone tools to the steel age and then to the space age, had proven that the revolution of materials is key for new technology development. Today, it is known that phenomenon such as interface delamination and de-bonding on a conventional thermal barrier coating (which are present in an environment with high temperature) degrades the performance of the material and its mechanical properties. In overcoming this adverse effects, two or more types of materials such as ceramic and metal are composed together creating a type of composite named Functionally Graded Material (FGM) in the literature. In studying the behavior of FGM, models based on a theoretical derivation of Euler-Bernoulli beam theory using the superposition method clearly demonstrate the superiority of two different configurations of FGM against the conventional coated beam. The FGM coated and under coated models apply a power-law function on the material properties across the FGM layers in comparing the effects of thermo-mechanical loading to those of conventional coated beam. Specifically, the results show that FGM drastically reduces stress concentration preventing the initiation of any delamination or de-bonding.